Efektifitas Media Pembelajaran MIPA Untuk Meningkatkan Hasil Pembelajaran Melalui Supervisi Akademik Di SMP N 3 Talamau - Yasman S.Pd (STKIP Pesisir Selatan, 2016)
AbstractBased on the observations that have been researchers did a teacher at SMP N 3 Talamau, it was found that the ability of teachers to make learning media is still low. The purpose of this study is to describe and obtain information about the effectiveness of learning Mathematics media to improve learning media Through Academic Supervision in SMP N 3 Talamau. This research is a school action. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of two teachers of SMP N 3 Talamau. Data were collected by using observation sheet. Data were analyzed using percentages. The results showed that the effectiveness of learning Mathematics media to improve learning outcomes through the Academic supervision in SMP N 3 Talamau function properly. This is evidenced by the increased effectiveness of learning Mathematics media to improve learning outcomes through the Academic supervision in SMP N 3 Talamau from the first cycle to the second cycle. The average ability of students and teachers in improving the effectiveness of instructional media in the first cycle was 57.27 with less category and the second cycle is 81.87 with both categories.Keywords: Effectiveness of Mathematics instructional media, Improve learning outcomes, Academic Supervision